2016
DOI: 10.1038/srep24059
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Psoriasis due to combined effect of HLA-Cw6 and LCE3 risk alleles in Indian population

Abstract: HLA-Cw6 is one of the most associated alleles in psoriasis. Recently, Late Cornified Envelop 3 (LCE3) genes were identified as a susceptibility factor for psoriasis. Some population showed epistatic interaction of LCE3 risk variants with HLA-Cw6, while some population failed to show any association. We determined the associations of a 32.2 kb deletion comprising LCE3C-3B genes and three SNPs (rs1886734, rs4112788; rs7516108) at the LCE3 gene cluster among the psoriasis patients in India. All three SNPs at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This highlights the need to use population-specific reference panels made by deep sequencing to impute MHC alleles and amino acids ( 8 ). The strong psoriasis risk of HLA-C*06:02 allele has been validated in worldwide populations including Europeans ( 17 , 20 ), East ( 6 , 21 ), and South Asians ( 22 ), with odds ratios of as high as 3.0–10.0. HLA fine-mapping analysis using the HLA imputation method successfully identified multiple other less obviously associated HLA-class I and class II variants that confer psoriasis risk independently from HLA-C*06:02 ( 20 ).…”
Section: Hla-class I Association Of Psoriasis: the Main Genetic Riskmentioning
confidence: 99%
“…This highlights the need to use population-specific reference panels made by deep sequencing to impute MHC alleles and amino acids ( 8 ). The strong psoriasis risk of HLA-C*06:02 allele has been validated in worldwide populations including Europeans ( 17 , 20 ), East ( 6 , 21 ), and South Asians ( 22 ), with odds ratios of as high as 3.0–10.0. HLA fine-mapping analysis using the HLA imputation method successfully identified multiple other less obviously associated HLA-class I and class II variants that confer psoriasis risk independently from HLA-C*06:02 ( 20 ).…”
Section: Hla-class I Association Of Psoriasis: the Main Genetic Riskmentioning
confidence: 99%
“…The worldwide HLA‐Cw6 allele frequency varies greatly and can range from 14·1% to 59·1%, whereas the percentage of patients with psoriasis carrying HLA‐Cw6 ranges from 10·5% to 77·2% (Table ) . Such wide ranges may be attributed to small sample sizes, ethnic diversity and differences in inclusion criteria.…”
Section: Hla‐cw6 Allele Frequency In Patients With Psoriasismentioning
confidence: 99%
“…PsV risk within MHC was originally mapped to a critical region at MHC class I, termed PSORS1 (Tiilikainen et al, 1980); then, HLA-C*06:02 was identified as the causal allele that explains the risk of PSORS1 (Nair et al, 2006). The strong PsV risk of HLA-C*06:02 allele has been validated in worldwide populations including Europeans (Lenz et al, 2015;Okada et al, 2014a), South Asians (Chandra et al, 2016), and East Asians (Mabuchi et al, 2014;Zhou et al, 2016), with an odds ratio (OR) of as high as 3.0e10.0. However, the genetic landscape of PsV within MHC has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%